2021
DOI: 10.3390/v13112261
|View full text |Cite
|
Sign up to set email alerts
|

Robust and Persistent B- and T-Cell Responses after COVID-19 in Immunocompetent and Solid Organ Transplant Recipient Patients

Abstract: The development and persistence of SARS-CoV-2-specific immune response in immunocompetent (IC) and immunocompromised patients is crucial for long-term protection. Immune response to SARS-CoV-2 infection was analysed in 57 IC and 15 solid organ transplanted (TX) patients. Antibody responses were determined by ELISA and neutralization assay. T-cell response was determined by stimulation with peptide pools of the Spike, Envelope, Membrane, and Nucleocapsid proteins with a 20-h Activation Induced Marker (AIM) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…At 240 days after the vaccine there was a significant difference in mean level of RBD S-protein IgG in previously SARS-CoV-2 infected subjects than in the uninfected individuals. This robust and persistent immunological response was probably the consequence of the memory B-cell and T-cell response to natural viral infection [ 7 ]. In this moment, it is unclear what the extent of antibody titers means for the risk of a future infection.…”
Section: Discussionmentioning
confidence: 99%
“…At 240 days after the vaccine there was a significant difference in mean level of RBD S-protein IgG in previously SARS-CoV-2 infected subjects than in the uninfected individuals. This robust and persistent immunological response was probably the consequence of the memory B-cell and T-cell response to natural viral infection [ 7 ]. In this moment, it is unclear what the extent of antibody titers means for the risk of a future infection.…”
Section: Discussionmentioning
confidence: 99%
“…The S-specific proliferative response was determined as previously described [3]. Briefly, PBMCs (600,000/200 µL culture medium per well) were stimulated in triplicate with S and human actin peptide pools (15 mers, overlapping by 10 amino acids, Pepscan, Lelystad, The Netherlands) at a final concentration of 0.1 µg/mL for 7 days.…”
Section: Detection Of S-specific T-cell Proliferative Responsementioning
confidence: 99%
“…Immunization against SARS-CoV-2, the causative agent of a global outbreak of a respiratory tract disease referred to as COVID-19, occurs via natural infection or vaccination. Several studies reported that higher titres of IgG and neutralising antibodies (Nt Ab) were detected in patients with severe SARS-CoV-2 infection compared to patients with mild symptoms [1][2][3][4][5][6][7]. SARS-CoV-2 spike (S) protein reactive T-cells were identified in immunocompetent (IC) patients suffering from moderate, severe, and critical COVID-19 [8], and a dominance of CD4 + T-cell over CD8 + T-cell response was observed in severe and mild COVID-19 patients [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations